Consumer spending trends to 2030 that businesses need to consider - Burlachuk, Lyudmila (My University, 2014)
Businesses need to take long term trends into account when planning ahead.
Keywords: споживач; тенденції витрачання; підприємства; consumer; spending trends; businesses; потребитель; тенденции расходования; предприятия